Energy developments: new forms, renewables, conservation proceedings of ENERGEX '84 , the global energy forum, Regina, Saskatchewan, Canada, May 14-19, 1984 - Curtis, Fred A. 1946- (Fred Allen) (Pergamon Press, 1984)
Energy Developments: New Forms, Renewables, Conservation is a collection of papers that discusses alternative energy sources. In discussing these energy sources, the text considers factors such as technical, economic, and human dimensions. The first part of the text presents articles that cover forms of energy, such as the feasibility of coal gasification and electric power from salinity gradients by reverse electrodialysis. Next, the book reviews materials about renewable forms of energy that include genetically improved hardwoods as a potential energy source and heat pump investigations for northern climate applications. In the last part, the text provides studies that deal with energy conservation, such as shared savings financing for energy efficiency and consumer information, and government energy conservation incentive programs. The book will be of use to scientists, engineers, and technicians involved in the research, development, and implementation of alternative energy technology.--Provided by publisher.